Gambaran Faktor Risiko Pasien Stroke Iskemik yang dirawat di Bangsal Saraf RSUD Arifin Achmad Provinsi Riau Periode 1 Januari 2018 31 Desember 2018 - Yossi Maryanti; Devi Susanti; Dhea Maulidyastuti (Fakultas Kedokteran Universitas Riau, 2019)
Ischemic stroke is neurological dysfuntion caused by focal cerebral, spinal, or retinal infarction with symptoms persisting for more than 24 hours. Prevalence of ischemic stroke is 87% of the total stroke. This study aims to describe the risk factors of ischemic stroke patients in neurology ward Arifin Achmad General Hospital Riau province 1 January 2018−31 December 2018 period. The cross sectional used in this study and the sampling methode was consecutive sampling. There was 150 cases in this study. The result shown that most of ischemic stroke patients at 51−65 year age group (52,0%), female (50,7%), have optimal total cholesterol levels (46,7%), optimal levels of LDL (28,0%), medium levels of HDL (55,3%), optimal levels of trygliceryde (66,0%), normal uric acid levels (63,3), have history of hypertension (60,0%), have not history of diabetes mellitus (72,7%) and history of heart disease (89,3%).